(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To evaluate the surgical outcomes of renal tumor resection using personalized 3D-printed kidney models at Hospital E from 2021 to 2024. Methods: A retrospective analysis of 16 patients who underwent laparoscopic renal tumor resection using personalized 3D-printed kidney models at Hospital E between April 2021 and February 2024 was conducted. Results: The study included 16 patients, comprising 8 males (50.0%) and 8 females (50.0%). The mean age was 61.7 years, with the majority of patients falling within the 60-69 age group (50%). Nine patients had left-sided renal tumors (56.2%) and seven patients had right-sided renal tumors (43.8%), with lower pole tumors exhibiting the highest prevalence (43.8%). The mean tumor size was 29x26x27mm. The mean surgical duration was 152 minutes. Laparoscopic retroperitoneal approach was employed in the majority of cases (14/16 cases, 87.5%). Three cases required radical nephrectomy (18.75%) due to tumor invasion of the renal pelvis. Open conversion was necessary in 2 cases (12.5%). Postoperative complications occurred in 3 cases (18.75%). Conclutions: Laparoscopic renal tumor resection utilizing personalized 3D-printed kidney models demonstrated favorable outcomes, characterized by short surgical duration, high nephrectomy preservation rate, and low complication rates.